2014
DOI: 10.1016/j.mayocp.2013.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Natural Disasters and Myocardial Infarction: The Six Years After Hurricane Katrina

Abstract: These results indicate that the effect of natural disasters on the occurrence of AMI may persist for at least a 6-year period and may be related to various factors including population shifts, alterations in the health care system, and the effects of chronic stress and associated behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 16 publications
(14 reference statements)
2
38
0
Order By: Relevance
“…These effects may persist for at least 6 years following a particular event and may be related to various factors including population shifts, alterations in the health care system, and the effects of chronic stress and associated behavior [6,16]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects may persist for at least 6 years following a particular event and may be related to various factors including population shifts, alterations in the health care system, and the effects of chronic stress and associated behavior [6,16]. …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there was a 3 fold increase in admissions for myocardial infarction incidence after the hurricane, an effect that persisted even 6 years after the event, thought to be related to various factors including population shifts, alterations in the health care system, and the effects of chronic stress and associated behaviors [6]. Reports of rates of post-traumatic stress disorder following tornadoes vary from 2% to 59% [7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown an increase in AMI during the immediate hours to weeks following natural disasters45. However, most studies have been conducted on the long-term effects of extreme weather events, such as Hurricane Katrina, which have been shown to be associated with an increased incidence of ACS occurring for up to six years after the hurricane134647. A single-center study found a 3-fold increase in the proportion of admissions for AMI in the 2 years following Katrina (2.18% vs. 0.71%, p < 0.0001), and also noted that the post-Katrina group had higher rates of unemployment, lack of insurance, medication non-compliance, smoking, and substance abuse13.…”
Section: Discussionmentioning
confidence: 99%
“…Studies about the effects of acute stressors have been performed in people that experienced disasters (earthquakes or hurricanes) [135, 136] while studies about chronic stressors evaluated, for example, the effects of job stress [137], marital unhappiness [138, 139], and burden of caregiving [140]. From all of these studies there are extensive data concerning stressors' contributions to diverse pathophysiological changes including sudden death, myocardial infarction, myocardial ischemia, and wall motion abnormalities, as well as to alterations in cardiac regulation as indexed by changes in sympathetic nervous system activity and hemostasis [140].…”
Section: The Stress Responsementioning
confidence: 99%